Borderline Lepromatous Leprosy with Severe Erythema Nodosum Leprosum: A Case Report - Nevristia Pratama; Luh Made Mas Rusyati; Prima Sanjiwani Saraswati Sudarsa; IGAA Dwi Karmila; NLP Ratih Vibriyanti Karna (Faculty of Medicine, Universitas Airlangga, 2022)
Background: Leprosy is a chronic granulomatous infectious disease caused by Mycobacterium leprae (M. leprae) that primarily infects Schwann cells in the peripheral nerves, leading to nerve damage and the development of disabilities. In 2018, Indonesia was the third country with the most leprosy cases in the world. Erythema nodosum leprosum (ENL), also known as type II leprosy reaction, is a severe immune-mediated complication of multibacillary leprosy. Purpose: To report a case of borderline lepromatous leprosy with severe ENL. Case: A 49-year-old Balinese man presented with multiple tender erythematous skin nodules all over his body, fever, arthralgia, bilateral cervical lymphadenopathy, and sensory loss for the past week. The acid-fast bacilli bacteriological examination showed a positive result. The patient was diagnosed with borderline lepromatous (BL) leprosy with severe ENL and was treated with multibacillary multidrug therapy (MB MDT), methylprednisolone, and other symptomatic medications. After 1 month of treatment, there was an improvement in skin lesions. The MB-MDT treatment was continued and methylprednisolone was planned to be tapered down gradually. Discussion: Approximately 20-50% of all leprosy patients show leprosy reactions in the course of the disease. The goals of treatment for severe ENL are to control inflammation, reduce pain, treat neuritis to prevent nerve dysfunction and contractures, and prevent recurring ENL. The prognosis of leprosy with ENL reactions depends on the severity of the occurring leprosy reaction; early diagnosis and prompt treatment; and patient compliance with treatment. Conclusion: Early diagnosis and treatment are essential to avoid deformities in leprosy patients.